Aspiration-related pneumonia after Taser exposure – A multiple causations mechanism. (September 2021) - Plenzig, S.; Verhoff, M.A.; Gruber, H.; Kunz, S.N.
Highlights: A 49-year old man with a complex medical history was shut with a Taser X26P and later died at the hospital. The present paper discusses several mechanisms of aspiration and alternation of consciousness in the context of CEW-exposure. The temporal proximity of CEW use and a person´s death does not prove their contribution in the causality of events. The cause and mechanism of death in ARD with CEW deployment usually is a multilayered combination of various factors. Abstract: Arrest-related deaths in the context of Conducted Electrical Weapon (CEW) deployment are rare. The evaluation of such complex events is a challenge for the forensic scientist. We present a case of a 49-year old man, who was exposed to a Taser X26P during a confrontation with the police. He lost consciousness, vomited, aspirated and died after having been hospitalized for several days at the ICU. Based on the patient´s medical history, autopsy findings, witness testimonies, and reliable clinical and toxicological blood parameters, the most probable cause and mechanisms of his death are discussed. The present work demonstrates, based on one case report, the possibilities as well as limitations of forensic assessment in CEW-related deaths.